Emergent and urgent otologic surgeries during the SARS-CoV-2 pandemic: a protocol and review of literature - Elise E. Zhao (KeAi Communications Co., Ltd., 2020)
Objective: To review guidelines for otologic procedures during the SARS-CoV-2 pandemic and to present a protocol for emergent or urgent mastoidectomy at our institution. Data sources: Guidelines regarding emergent and urgent otologic procedures from otolaryngologic societies are reviewed. We described a protocol for emergent or urgent mastoidectomy at our institution. Conclusion: Patients requiring urgent or emergent mastoidectomy during the COVID-19 pandemic require prompt treatment. We make the following recommendations: Emergent or urgent otologic procedures should be performed in a contained environment, such as a tent created by the microscope drape. The surgical team should practice using instruments in the tent setup to prepare for real cases. Otologic procedures should adhere to guidelines set for high-risk procedures.